Effect of incremental equal channel angular pressing (I-ECAP) on the microstructural characteristics and mechanical behaviour of commercially pure titanium. (15th May 2017) - Qarni, Muhammad Jawad; Sivaswamy, Giribaskar; Rosochowski, Andrzej; Boczkal, Sonia
Abstract: Incremental equal channel angular pressing (I-ECAP) is one of the continuous severe plastic deformation (SPD) processes. This paper presents the processing of commercial purity titanium (CP-Ti) using a double billet variant of I-ECAP process. Ultrafine-grain (UFG) structure was successfully achieved after six passes of I-ECAP at 300 °C. Microstructural evolution and texture development were tracked using EBSD. Analysis revealed continuous dynamic recrystallization (CDRX) as one of the grain refinement mechanism during processing. Room temperature tensile tests carried out before and after six passes, shows significant increase in strength with acceptable levels of ductility. The yield strength was increased from 308 to 558 MPa and ultimate tensile strength from 549 to 685 MPa. Compression tests conducted at different strain rates shows considerable increase in strength and enhanced strain rate sensitivity after processing. A distinct three-stage strain hardening was observed during compression. However the processed material displayed a loss in strain hardening ability during tensile as well as in compression tests. Detailed microhardness measurements show the evolution of hardness after subsequent passes with a reasonable level of homogeneity after the sixth pass. It is demonstrated that I-ECAP is an effective method for grain refinement in CP-Ti and subsequently improving its mechanical properties. Graphical abstract: Highlights: Commercial purity titanium was processed via incremental equal channel angular pressing at 300 °C. The grain refinement achieved was in the ultrafine grain size range and CDRX was a dominant mechanism for grain refinement. Significant increase in yield and ultimate tensile strength was achieved with minimal loss of ductility. Compression tests at various strain rates reveal a distinct three-stage strain hardening behaviour. The processing yielded noticeable increase in hardness characteristics.